Prey capture in zebrafish larvae serves as a model to study cognitive functions - Muto, Akira; Kawakami, Koichi (Frontiers in Neural Circuits, 2013)
Prey capture in zebrafish larvae is an innate behavior which can be observed as early as 4~days postfertilization, the day when they start to swim. This simple behavior apparently involves several neural processes including visual perception, recognition, decision-making, and motor control, and, therefore, serves as a good model system to study cognitive functions underlying natural behaviors in vertebrates. Recent progresses in imaging techniques provided us with a unique opportunity to image neuronal activity in the brain of an intact fish in real-time while the fish perceives a natural prey, paramecium. By expanding this approach, it would be possible to image entire brain areas at a single-cell resolution in real-time during prey capture, and identify neuronal circuits important for cognitive functions. Further, activation or inhibition of those neuronal circuits with recently developed optogenetic tools or neurotoxins should shed light on their roles. Thus, we will be able to explore the prey capture in zebrafish larvae more thoroughly at cellular levels, which should establish a basis of understanding of the cognitive function in vertebrates.